DETECTION OF Campylobacter coli BY LOOP MEDIATED ISOTHERMAL AMPLIFICATION ASSAY FROM BROILER CHICKENS - Kavin Gunasekaran; M. Ananda Chitra; T.V. Meenambigai; K. Shoba (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Campylobacter spp. are the most common cause of foodborne illnesses and bacterial enteritis across the globe. Poultry harbours this pathogen the most and transmit them to human beings. Being the fastidious organism, isolation and detection of Campylobacter is time consuming and difficult. In this study, the most common species - Campylobacter coli was detected using Loop Mediated Isothermal Amplification assay (LAMP). A total of 191 broiler chicken caecal samples, after presumptive identification of Campylobacter, were subjected to LAMP assay with colorimetric detection. Out of 191 samples collected, 14 were found positive for C. coli. LAMP assay takes only around 45 min after extraction of DNA to detect C. coli.  LAMP assay aids in rapid detection of C. coli isolates and does not require any sophisticated instruments. Thus, LAMP assay is a simple and rapid detection method for Campylobacter coli can be performed in any basic clinical laboratory.